Genetic correlations between heifer subsequent rebreeding and age at first calving and growth traits in Nellore cattle by Bayesian inference - Boligon, A. A. [UNESP]; Baldi, Fernando [UNESP]; Albuquerque, Lucia Galvão de [UNESP] (Funpec-editora, 2012)
We estimated heritability for subsequent rebreeding (SR) of heifers and genetic correlations between this trait and weaning weight (WW), weight gain from weaning to yearling (WG), age at first calving (AFC), and mature cow weight (MW), in order to evaluate whether SR could be included as selection criterion in Nellore cattle. The SR of heifers was defined by attributing a value of 1 (success) or 0 (failure) to heifers that calved or not, respectively, given that they had calved once before. Records from 127,430 Nellore animals were analyzed. Genetic parameters were estimated by Bayesian inference using a nonlinear (threshold) animal model for SR and a linear animal model for the other traits in three-trait analyses, including SR and WW in all analyses. The posterior means of heritability for SR, WW, WG, AFC, and MW were 0.18 +/- 0.02, 0.21 +/- 0.01, 0.30 +/- 0.01, 0.21 +/- 0.01, and 0.45 +/- 0.04, respectively. The posterior mean estimates of genetic correlations between SR and WW, WG, AFC, and MW were -0.20 +/- 0.06, 0.31 +/- 0.07, -0.77 +/- 0.05, and -0.15 +/- 0.09, respectively. Based on these genetic correlations, selection for higher gains for WG and younger AFC should result in an increase in heifer SR rates, while long-term selection for increasing WW should promote unfavorable responses in heifer SR. The use of breeding values for heifer SR as a selection criterion of Nellore bulls could increase heifer SR rate without significant changes in MW.
Keywords: Bayesian inference; Beef cattle; Fertility; Genetic parameter